Ion-induced formation of micropolycrystalline Nb1-xCx (0 ≤ x < 0.3) thick coatings with quasi-ternary phase structure - Sleptsov, S.N.; Sleptsov, A.N. (Вопросы атомной науки и техники, 2001)
Structure and superconductivity of thick polycrystalline niobium-carbon coatings (Nb1-xCx, 0 ≤ x < 0.3) deposited from low-energy self-ion-atomic Nb- and C- fluxes onto substrates with the temperature range 500…650 K were studied by X-ray diffraction (XRD) analysis, transmission electron microscopy (TEM), electron diffraction, TEM of oxidic replicas and resistivity measurement method at low temperature. It is founded, that Nb1-xCx coatings with carbon concentration range 9…15 at.% have an unusual high superconducting transition temperature Tc ≈ 12 K. Dependency of critical current density of these coatings on temperature is not monotonous and have a sharp bend near TC ≈ 9.5 K Structural analysis of these coatings has revealed they have a quasi-ternary phase composition consisting of Nb(b.c.c.), subcarbide Nb₂C(c.p.h.) and metastable carbide 'NbCx' with f.c.c. structure. The results obtained are discussed from a point of view of 'NbCx' phase forming at Nb and Nb₂C phases interface. It is also shown, that Nb1-xCx coatings with carbon concentration less than 5 at.% revealed supersaturated solid solution and have TC ≈ 9.5 K. Kinetics of diffusive decomposition of niobium-carbon coatings during isothermal annealing was also investigated. Структура та надпровідність товстих полікрісталічних ніобій-вуглецевих покриттів (Nb1-xCx, 0 ≤ x < 0,3), осаджених із низькоенергетичних самоіонних-атомних Nb- и C- потоків на підкладки у температурному інтервалі 500...650 К були вивчені за допомогою рентгеноструктурного аналізу, просвічуючи електронної мікроскопії окісних реплік та методом вимірювання питомого опору при низький температурі. Було встановлено, що Nb1-xCx покриття з концентрацією вуглецю в інтервалі 9...15 ат.% мають надзвичайно високу температуру надпровідного переходу Тс ≈ 12 К. Залежність критичної щільності цих покриттів від температури не є монотонною і виявляє крутий ізгіб величин біля Тс ≈ 9,5. Структурний аналіз цих покриттів показав, що вони мають квазіпотрійний фазовий склад, що складається із Nb(ОЦК), субкарбіда Nb₂C (ГПУ) та метастабільного карбіду NbCx з ГЦК-структурою. Отриманы результати обговорюються з точки зору NbCx -фази, яка утворюється на поверхні розподілу Nb та Nb₂C-фаз. Показано також, що Nb1-xCx -покриття з концентрацією вуглецю нижче 5 ат.% виявляють пересичений твердий розчин і мають Тс ≈ 9,5 К. Була також досліджена кінетика фаз дифузного розкладу ніобій-вуглецевих покриттів у процесі ізотермічного відпалу. Структура и сверхпроводимость толстых поликристаллических ниобий-углеродных покрытий (Nb1-xCx, 0≤ x <0,3),
осажденных из низкоэнергетических самоионных-атомных Nb- и C- потоков на подложки в температурном интервале
500…650 К, были изучены рентгеноструктурным анализом (ХRD), просвечивающей электронной микроскопией (TEM),
дифракцией электронов, просвечивающей микроскопией окисных реплик и методом измерений идеального сопротивления при низкой температуре. Было установлено, что Nb1-xCx покрытия c концентрацией углерода в интервале 9…15 ат.%
обладают необычно высокой температурой сверхпроводящего перехода Тс∼12 К. Зависимость критической плотности
этих покрытий от температуры не является монотонной и обнаруживает крутой изгиб около Тс≈9,5 К. Структурный анализ этих покрытий показал, что они имеют квазитройной фазовый состав, состоящий из Nb (ОЦК), субкарбида Nb₂C
(ГПУ) и метастабильного карбида NbCx c ГЦК-структурой. Полученные результаты обсуждаются с точки зрения NbCx
-фазы, формирующейся на поверхности раздела Nb- и Nb₂C- фаз. Показано также, что Nb1-xCx- покрытия с концентрацией углерода ниже 5 ат.% обнаруживают перенасыщенный твердый раствор и имеют Тс ≈ 9,5 К. Была также исследована
кинетика диффузного разложения ниобий-углеродных покрытий в процессе изотермического отжига.